Quality Function Deployment (QFD) and TRIZ in Briquette Cookstove Design and Simulation - Faria, Niswatun; Ummatin, Kuntum Khoiro; Junianto, Mochammad Annas; Budiharso, Tedy Eko (Jurnal Rekayasa Mesin, 2021)
Poor cookstove design can harm the user's health and environment. This research aims to obtain an efficient cookstove design, environmentally friendly and operated easily. The cookstove design process using a combination ofÂ  QFD and TRIZ. QFD able to capture customer needs through a questionnaire and interview. The data collected then processed to build a House of Quality (HoQ), one of the tools in QFD. QFD results in the design parameter of the briquette cookstove, which is incorporated in the concept design. The TRIZ method is utilized to understand the problem that might occur in the concept design and focus on solving the root causes. The next step is a detailed design where the dimensions, combustion chamber capacity, and supporting features are explained. The combination of QFD and TRIZ result in a briquette cookstove concept design which is easy to clean and operate. The combustion system is Top-lit Up-Draft (TLUD). The burning chamber has two air inlets, namely primary and secondary. The primary air inlet supplies the air from the bottom of the burning chamber, partially burns the briquette, and produces flue gas. The secondary air inlet is in the shape of an oval to supply air in the burning chamber's upper part to burn the flue gas completely. A complete combustion process will increase combustion efficiency and reduce emissions. A computational simulation shows the velocity distribution inside the burning chamber.